Experimental study into erosion damage mechanism of concrete materials in a wind-blown sand environment - Hao, Yunhong; Feng, Yujiang; Fan, Jincheng (Construction & building materials, 2016)
•The concrete erosion rate increases with the impact velocity and the impact angle.•The erosion rate is most obvious as the abrasive feed rate at a certain range.•Erosion of concrete has no apparent incubation period but has a rising and stable period.•It can predict the actual erosion time by similarity analysis. Based on the knowledge that concrete structures in the mid-west of Inner Mongolia are subject to erosion caused by the wind and sand environment over a long period of time, sediment-air injection method was used for an experimental study into erosion on concrete in the wind-blown sand environment, and then involving analysis of concrete erosion features and erosion behavior law. The results show that: The erosion rate increases with the increasing impact velocity, the two have an empirical power law relationship, and under same erosion condition, it is found that the velocity exponent (n) in the erosion rate equation (E=kVn) increases with the increasing concrete strength; as the impact angle increases, the concrete erosion rate also increases; the erosion resistance of concrete is first decreasing then increasing with the erodent feed rate, the erosion rate is most obvious as the abrasive feed rate at a certain range (in this paper, the abrasive feed rate is around 90g/min); under the same conditions, for concretes with different strengths, the erosion rate decreases with an increase in strength; erosion of concrete has no apparent incubation period but has a rising and stable period, and the accumulative mass loss due to erosion almost increases linearly. The surface micrograph of concrete specimen after erosion were observed by scanning electron microscope (SEM), then the concrete erosion damage mechanism was discussed and it was proposed that there were two mechanisms: surface scratch failure mechanism at low impact angles and impact indentation crushing mechanism at high impact angles during the concrete erosion, which can provide an explanation for failure of concrete materials. The relationship between the experimental results and the actual wind-blown sand erosion conditions was obtained by similarity analysis.